Forecasting paediatric malaria admissions on the Kenya Coast using rainfall - Karuri, SW; Snow, RW (Taylor & Francis Open, 2016)
Background Malaria is a vector-borne disease which, despite recent scaled-up efforts to achieve control in Africa, continues to pose a major threat to child survival. The disease is caused by the protozoan parasite Plasmodium and requires mosquitoes and humans for transmission. Rainfall is a major factor in seasonal and secular patterns of malaria transmission along the East African coast.